Analogies Between Nuclear Physics and Dark Matter - Gamboa-Rios, J; Riveros-Rodriguez, A (World Scientific Publishing Co. Pte Ltd, 2014)
A fermionic description of dark matter using analogies with nuclear physics is developed. At tree level, scalar and vector processes are considered and the two-body potential are explicitly calculated using the Breit approximation. We show that the total cross-sections in both cases exhibit Sommerfeld enhancement. © 2014 World Scientific Publishing Company.